2004
DOI: 10.1111/j.1365-2567.2004.01937.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipid‐associated membrane proteins of Mycoplasma fermentans and M. penetrans activate human immunodeficiency virus long‐terminal repeats through Toll‐like receptors

Abstract: SUMMARYMycoplasmas are known to enhance human immunodeficiency virus (HIV) replication, and mycoplasma-derived lipid extracts have been reported to activate nuclear factor-jB (NF-jB) through Toll-like receptors (TLRs). In this study, we examined the involvement of TLRs in the activation of HIV long-terminal repeats (LTR) by mycoplasma and their active components responsible for the TLR activation. Lipid-associated membrane proteins (LAMPs) from two species of mycoplasma (Mycoplasma fermentans and M. penetrans)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 65 publications
2
37
0
Order By: Relevance
“…Furthermore, the resistance to Edman degradation of proteins from M. mycoides also indicates the presence of N acylation (5). We previously showed that lipoproteins from M. fermentans enhance human immunodeficiency virus replication through TLR2 and TLR6 but lipoproteins from M. penetrans facilitate human immunodeficiency virus replication through TLR1, TLR2, and TLR6 (42). We also reported that the lipoproteins isolated from M. pneu- 293T cells were transfected with 0.2 g/ml of pFLAG-dTLR6 or pFLAG-dTLR1, 0.01 g/ml of pFLAG-TLR2, 0.01 g/ml of pNFkB-luc, and 0.01 g/ml of pRL-TK.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the resistance to Edman degradation of proteins from M. mycoides also indicates the presence of N acylation (5). We previously showed that lipoproteins from M. fermentans enhance human immunodeficiency virus replication through TLR2 and TLR6 but lipoproteins from M. penetrans facilitate human immunodeficiency virus replication through TLR1, TLR2, and TLR6 (42). We also reported that the lipoproteins isolated from M. pneu- 293T cells were transfected with 0.2 g/ml of pFLAG-dTLR6 or pFLAG-dTLR1, 0.01 g/ml of pFLAG-TLR2, 0.01 g/ml of pNFkB-luc, and 0.01 g/ml of pRL-TK.…”
Section: Discussionmentioning
confidence: 99%
“…The data are the means (ϮSD) from four independent experiments using different donors. 134,139,161). Therefore, the use of the synthetic TLR2 ligand PAM3CSK4 recapitulates the contribution of other STI cofactors on HIV-1 replication in macrophages.…”
Section: Nr Ligands Inhibit Hiv-1 Replication In Primary Macrophagesmentioning
confidence: 99%
“…In contrast, TLR1-deficient cells show a normal response to mycoplasma-derived diacylated lipopeptides, but an impaired response to triacylated lipopeptides. Shimizu et al(2004) found that the purified lipoprotein of M. penetrans LAMPs was able to activate NF-κB through TLR1 and TLR2. On the other hand, the activation of NF-κB by the purified lipoproteins of M. fermentans LAMPs was mediated through TLR2 and TLR6, but not TLR1.…”
Section: Cooperative Interactions Among Tlrsmentioning
confidence: 99%
“…This suggests that the active components are attributed to lipid moieties, although the moieties of proteins might have other functions (Shimizu et al, 2004). The acylated proteins of mycoplasmas are abundant cell-surface antigens, which are recognized by extra-cellular domains of TLRs.…”
Section: Signaling Pathway Triggered By Mycoplasma Lipoproteins Throumentioning
confidence: 99%